2019
DOI: 10.15446/ts.v21n2.74641
|View full text |Cite
|
Sign up to set email alerts
|

Migraciones, estereotipos y rumores: combatiendo la Hidra-xenofóbica en Andalucía

Abstract: Este artículo describe el proyecto de la Red Anti-Rumores de Andalucía creada para combatir los prejuicios, estereotipos y rumores relacionados con las migraciones. Se exponen las características de las migraciones en Andalucía, los resultados de estudios de opinión de la población sobre esta realidad social y cómo determinados estereotipos que se reproducen en forma de rumores originan actitudes de rechazo, perjudicando gravemente la convivencia en una sociedad multicultural. Se concluye que la Red debe forta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…According to Rodríguez et al (2018), attitudes, prejudices, and stereotypes of this kind can lead to Islamophobia. Among the most common stereotypes are those of immigrants taking jobs from locals, abusing social resources, and overwhelming the health care system (Jiménez-García & Jimenez-Vicioso, 2019). Nevertheless, the perception of immigrants as a threat is influenced by the economic conditions experienced in a country at a given time.…”
Section: Introductionmentioning
confidence: 99%
“…According to Rodríguez et al (2018), attitudes, prejudices, and stereotypes of this kind can lead to Islamophobia. Among the most common stereotypes are those of immigrants taking jobs from locals, abusing social resources, and overwhelming the health care system (Jiménez-García & Jimenez-Vicioso, 2019). Nevertheless, the perception of immigrants as a threat is influenced by the economic conditions experienced in a country at a given time.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we also found the rise of this preconception of abuse of migrants of the health system, making them responsible for the saturation in health centers [28]. This idea is far from the truth, as shown by the studies conducted on these aspects.…”
Section: Discussionmentioning
confidence: 52%
“…This information is relevant insofar as the image of a specific group held by a society is reflected both among student nurses [17,18] and qualified nurses, as revealed by the authors of several studies undertaken in hospital settings [9,19], and similarly in a study on the attitudes of student nurses in Portugal [20]. Such attitudes can have a negative impact on the care process for patients from different cultures [14,15,21,22].…”
Section: Introductionmentioning
confidence: 99%